Urban Water Demand on Interbasin Water Resources Management System - Sutoyo .; M. Yanuar J. Purwanto; Kato Tasuku; Goto Akira (PERTETA, 2009)
Cidanau watershed in West of Java has 22,620 ha; it provides water for other basin in the largestindustrial city of Cilegon. To have future condition of water supply and demand for Cidanau and Cilegonregion model was developed expressing water supply from Cidanau built by tank model with some landuses related parameters. Water supply from Cidanau watershed depends on land use and water systemin the watershed. The rest of water flow to the downstream and be utilized to the Cilegon city by Cinangkapump station and calculated based on the water use of industrial and domestic. To maintain and increasethe availability of water, it is necessary to change some land uses into forest and install better water supplysystem with higher efficiencies. Water availability of runoff under existing condition as Scenario 1 is onlysufficient until before the year 2018. Scenario 2 with the land use to be change as 50% of the mixedagricultural dry land system into forest area and 50% garden into rice field, water availability will be sufficientuntil more than 2018. If Scenario 2 was used together with Scenario 3 having better efficient technology,water supply will be sufficient until more than the year 2025.Keywords : water supply, water demand, urban, interbasin, system dynamicsDiterima: 7 Januari 2009; Disetujui: 14 Juli 2009